The Mediating Role of Affective Commitment in the Relationship Between Ethical Leadership and Ethical Climate in Non-Profit Sports Organizations in Ardabil Province - Esmaeili Lemjiri, Fatemeh; Rahimi Ani Sofla, Parisa; Alshomar, Al_ Zahra (International Journal of Business Management and Entrepreneurship, 2025)
The research was conducted to examine the effect of ethical leadership on ethical climate with the mediation of emotional commitment in non-profit sports organizations of Ardabil province. The study has been conducted on members from non-profit sport organizations of Ardabil province. This cross-sectional study was conducted using three questionnaires of ethical leadership behavior Brown et al. (2005), ethical climate Victor and Cullen (1988) and De Waal (2018) affective organizational commitment on the Likert scale to collect data. Data has been collected from 157 employees through a pretested questionnaire. Data from the cross-sectional study was analyzed using SPSS 24. For testing the hypothesis, Hayes Process mediation model has been applied. Findings have revealed that affective organizational commitment in both forms of strategies are significantly and positively related to ethical climate. Further, affective organizational commitment has been identified as a significant mediator between ethical leadership behavior and ethical climate with full mediation effect. It can be concluded that if organizations have a very ethical atmosphere, it can improve emotional commitment. It is a fact that ethical leadership behavior influences ethical climate directly and indirectly through affective commitment.